Inoperable chronic thromboembolic pulmonary hypertension treated with riociguat: A case studyInoperable chronic thromboembolic pulmonary hypertension - Carlos Ortiz-Bautista (Revista Portuguesa de Cardiologia (English Edition), 2015)
A 51-year-old woman presented with a one-year history of progressive dyspnea, WHO functional class III-IV and exercise-related syncope. Transthoracic echocardiography and computed tomography pulmonary angiography were performed, leading to a diagnosis of pulmonary arterial hypertension. She was referred to our pulmonary hypertension unit, where a complete study was performed, including ventilation/perfusion scan, which was consistent with chronic thromboembolic pulmonary hypertension. Risk factors for this condition were excluded and therapeutic options were evaluated. Imaging studies showed distal pulmonary disease so pulmonary endarterectomy was rejected. Further therapeutic options were evaluated and the patient was subsequently enrolled in an open-label uncontrolled trial with riociguat. After one year of treatment, significant improvement in functional class, 6-minute walk test and NT-proBNP were seen, without significant secondary effects. Resumo: Uma mulher de 51 anos de idade apresentou-se com história de um ano de dispneia progressiva com classe funcional III-IV e síncope relacionada com exercício. A ecocardiografia transtorácica e a angiotomografia pulmonar computadorizada foram realizadas, tendo sido diagnosticada hipertensão arterial pulmonar. A doente foi encaminhada para a Unidade de Hipertensão Pulmonar, onde foi repetido o estudo completo, incluindo verificação de ventilação/perfusão, compatível com hipertensão pulmonar tromboembólica crónica. Os fatores de risco para essa situação foram excluídos e foram avaliadas as opções terapêuticas. Estudos de imagem mostraram doença pulmonar distal pelo que a endarterectomia pulmonar foi rejeitada. Foram avaliadas novas opções terapêuticas e a doente foi posteriormente inscrita num estudo aberto, não controlado, com ensaio com riociguat. Após um ano de tratamento, uma melhoria significativa na classe funcional, um teste de caminhada de 6 minutos e NT-proBNP foram alcançados sem efeitos secundários significativos. Keywords: Chronic thromboembolic pulmonary hypertension, Treatment with riociguat, Safety profile of riociguat, Palavras-chave: Hipertensão pulmonar tromboembólica crónica, Tratamento com riociguat, Perfil de segurança do riociguat